ROLE OF EMPLOYEES IN IMPLEMENTATION OF NEW TECHNOLOGY-BASED HUMAN RESOURCE INFORMATION SYSTEM USED BY LARGE-SCALE MANUFACTURING ORGANIZATIONS IN SOUTH EAST RAJASTHAN (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
This study examines the role of various employee attributes in the effective utilization of Human Resource Information Systems (HRIS) within large-scale manufacturing organizations in South-East Rajasthan. Data were collected from a sample of 620 employees across eight major manufacturing companies using a simple random sampling technique. These organizations—including CFCL, DCM, JK Cement, Mangalam Cement, ACC, Shriram Rayons, Wonder Cement, and Sangam India Ltd.—utilize diverse HRIS software systems such as SAP HANA, SAP, SAP Accent, Darwin Box, and PeopleStrong. The findings, derived through analysis of variance (ANOVA) and post hoc statistical testing, reveal significant differences in employee perceptions and self-efficacy toward HRIS across organizations. Key factors influencing HRIS effectiveness were identified as employee engagement, organizational training support, and the level of digital readiness. Notably, organizations such as Shriram Rayons demonstrated higher employee self-efficacy and more effective HRIS utilization, whereas companies such as CFCL exhibited relatively lower engagement. The study concludes that employees play a pivotal and strategic role in the successful implementation and adoption of HRIS. Their active involvement, confidence, and access to appropriate training significantly influence the system’s efficiency and integration. These insights emphasize the necessity for organizations to invest in continuous capacity building initiatives, inclusive implementation practices, and employee-centered strategies to enhance the overall effectiveness of HRIS in human resource operations.
Keywords: HRIS, motivation, self-efficacy, SAP, strategic role